1996
DOI: 10.1016/0014-5793(96)00929-5
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of nuclear alkaline phospholipase A2 in rat ascites hepatoma cells

Abstract: The alkaline phospholipase A2 (PLA2) was purified from nuclei of rat ascites hepatoma cells (AH7974) by column chromatography with a Sephacryl S-300 column and an immunoadsorbent using anti-group II PLA2 monoclonal antibody. From these two columns, the alkaline PLA2 was eluted in parallel with a 17-kDa protein which is reactive to another antigroup II PLA2 polyclonal antibody. Approximately 80% of nuclear PLA2 was inhibited by this antibody. The alkaline PLA2 was found in association with the chromatin fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The homogeneity of the nuclear preparations was established by staining with propidium iodide, which specifically stains DNA (Figure 8), and found to be pure at this level of resolution. Furthermore, assessment of subcellular marker enzyme activities (Table 1) demonstrated that the nuclear preparations were relatively free of contamination by golgi and endoplasmic reticulum and comparable in terms of purity to that obtained by others (29,30). Incubation of nuclei with Ab 1073 resulted in intense staining characterized by a stippled, punctate pattern.…”
Section: Identification Of ␤Ig-h3 In the Nucleus Of Hbsm Cellssupporting
confidence: 63%
“…The homogeneity of the nuclear preparations was established by staining with propidium iodide, which specifically stains DNA (Figure 8), and found to be pure at this level of resolution. Furthermore, assessment of subcellular marker enzyme activities (Table 1) demonstrated that the nuclear preparations were relatively free of contamination by golgi and endoplasmic reticulum and comparable in terms of purity to that obtained by others (29,30). Incubation of nuclei with Ab 1073 resulted in intense staining characterized by a stippled, punctate pattern.…”
Section: Identification Of ␤Ig-h3 In the Nucleus Of Hbsm Cellssupporting
confidence: 63%
“…6) suggests that the caveolae-mediated endocytotic event called potocytosis occurs in cytokine-stimulated cells. Several previous subcellular fractionation studies demonstrated the pres- ence of significant sPLA 2 -IIA in some intracellular organelle fractions including the nucleus (52,57). The perinuclear localization of sPLA 2 -IIA is also supported by the fact that glypican-1, an sPLA 2 -IIA-adaptor protein, has a bipartite motif for nuclear localization signals (37).…”
Section: Discussionmentioning
confidence: 59%
“…After incubation for 30 min at 4°C, the crude nuclear fraction was obtained by low spin centrifugation at 450 ϫ g, as reported previously (52). The remaining supernatants were centrifuged for 1 h at 100,000 ϫ g at 4°C, and the resulting supernatants were applied to a rabbit anti-sPLA 2 -IIA antibody-conjugated Sepharose column.…”
Section: Methodsmentioning
confidence: 99%
“…This correlation will be elucidated by the in vivo experiments for direct detection of the specific phosphorylation of cellular sPLA 2 -IIA with membrane-associated CK-II 17) in interleukin-1 (IL-1)/tumor necrosis factor (TNF)-stimulated cells. This possibility is strongly supported by the following recent reports: (i) sPLA 2 -IIA is the most widely distributed isozyme in humans and rats, 20) and is extremely induced by proinflammatory stimuli, such as bacterial endotoxin, IL-1 and TNF 21) ; (ii) this isozyme is localized in the punctate and perinuclear domains in IL-1/TNF-stimulated cells and is accumulated in the caveolae of cytokine-stimulated cells; 22,23) and (iii) caveolae are highly enriched in caveolins (structural proteins), b 2 -adrenergic receptor, cAMP-dependent protein kinase (A-kinase) 24) and receptor tyrosine kinases, such as platelet-derived growth factor receptor 25) and ErbB receptor, 26) corresponding signal transduction for metabolic and mitogenic effects, and functions as a lipid scaffold for organizing the molecular interactions of multiple signaling pathways. 27) For understanding clearly the biochemical mechanism involved in the GL-induced anti-inflammatory effect in vivo, further analytical studies will be required (i) to confirm a GL-sensitive sPLA 2 among at least five isozymes (sPLA 2 -IIA, sPLA 2 -IIC, sPLA 2 -IID, sPLA 2 -IIE and sPLA 2 -IIF) 28,29) of the sPLA 2 -II family in various clinical materials, such as synovial fluid of patients with rheumatoid arthritis and sera of patients with autoimmune diseases; (ii) to characterize the regulatory mechanism of the GL-sensitive sPLA 2 by membrane-associated CK-II or other protein kinases [A-kinase, Ca 2ϩ /phospholipid-dependent protein kinase (C-kinase), mitogen-activated protein kinase (MAP-kinase) and receptor tyrosine kinases] in vivo and in vitro; and (iii) to determine the suppressive effects of GL, GA and oGA on the induction of a GL-sensitive sPLA 2 in the cytokine-mediated response at the cellular level.…”
Section: Discussionmentioning
confidence: 71%